Pengaruh Pengumuman Earnings Terhadap Abnormal Return Saham - Sheila Virginia; Elizabeth Tiur Manurung; ~ Muliawati (Jurnal Administrasi Bisnis, 2012)
Investors invest in capital market to get return. In order to get it, they must makeinvestment decision (buy, hold, or sell stock) based on available information. One ofthe information that is available in capital market is earnings information. We caninfer that earnings announcement has information content based on market reactionshowed by significant abnormal return in the event period. Besides that, based onspeed of market reaction to earnings announcement we can know if Indonesian cap-ital market is efficient or not. This research also study how significant of earningsannouncement to stock’s abnormal return. Finally, this research compare abnormalreturn between group of sample who announced increase in profit and group ofsample who announced decrease in profit.Keywords: earnings, abnormal return